Levels of C-Reactive Protein and Protein C in Periodontitis Patients with and without Cardiovascular Disease - ALTURFAN, EBRU IŞIK (KARGER, 2009)
Since periodontitis is a chronic and inflammatory disease, a number of hypotheses have proposed that it has an etiological or modulating role in cardiovascular disease (CVD). This study aimed to ascertain the changes in the plasma levels of C-reactive protein (CRP) and protein C (PC), a natural anticoagulant also having an anti-inflammatory effect, in patients who have mild-to-severe periodontitis with or without CVD. The test group consisted of 26 patients with CVD and chronic periodontitis and the control group consisted of 26 patients with chronic periodontitis and no systemic disease. In both groups Community Periodontal Index of Treatment Needs scores were recorded and blood samples were collected. CRP levels were significantly high and PC activity was significantly low in the test group compared to the control group (p < .001). There was a negative correlation between tooth loss and PC and between CRP and PC. How PC is affected by the inflammatory events and its association with CRP is an active area of investigation. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Periodontitis; Community Periodontal Index of Treatment Needs; Cardiovascular disease; C-reactive protein; Protein C